2017
DOI: 10.3748/wjg.v23.i32.5875
|View full text |Cite
|
Sign up to set email alerts
|

Nano albumin bound-paclitaxel in pancreatic cancer: Current evidences and future directions

Abstract: Pancreatic cancer (PDAC) is an aggressive and chemoresistant disease, representing the fourth cause of cancer related deaths in western countries. Majority of patients have unresectable, locally advanced or metastatic disease at time of diagnosis and the 5-year survival rate in these conditions is extremely low. For more than a decade gemcitabine has been the cornerstone of metastatic PDAC treatment, although survival benefit was very poor. PDAC cells are surrounded by an intense desmoplastic reaction that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 75 publications
(73 reference statements)
0
66
0
Order By: Relevance
“…3). Nano albumin-bound (nab) paclitaxel delivers a high concentration of paclitaxel within pancreatic tumors, resulting in the inhibition of microtubule depolymerization and cancer cell division [134,135]. Benefiting from the synergistic effects [136,137], the clinical application of nab paclitaxel often occurs in combination with gemcitabine.…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
“…3). Nano albumin-bound (nab) paclitaxel delivers a high concentration of paclitaxel within pancreatic tumors, resulting in the inhibition of microtubule depolymerization and cancer cell division [134,135]. Benefiting from the synergistic effects [136,137], the clinical application of nab paclitaxel often occurs in combination with gemcitabine.…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
“…New drug delivery approaches are effective in order to provide a high local concentration of the anticancer drug, enhance the efficacy of chemotherapy, as well as to reduce systemic side effects. Numerous papers have been published in the field of drug delivery carriers that validate their superior anti-tumor effect (Chakravarty et al, 2015;Croft et al, 2018;Giordano et al, 2017;Lu et al, 2014;Raza et al, 2018;Werner et al, 2013). Recently, we reported on a novel biodegradable N-Butyl-2-cyanoacrylate-based injectable in situ-forming implants, formed from n-butyl-2-cyanoacrylate (NBCA) and ethyl oleate.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, a blockade of PTEN has shown a critical rationale beyond other anti-pancreatic cancer strategies. Treatment with chemotherapeutics such as gemcitabine, FOLFIRINOX, and nanoparticle albumin-bound paclitaxel (nAb-PTX) have been reported to induce severe side effects including anemia, depilation, diarrhea, and vomiting in almost all patients [22][23][24][25][26][27][28][29]. In our study, we demonstrated that targeting PTEN had no basal cytotoxicity on the human pancreatic duct epithelial cell line H6c7, which induced the viability and migration features of H6c7 cells.…”
Section: Discussionmentioning
confidence: 66%